2004
DOI: 10.1002/jppr200434126
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Care: Impact on Asthma Medication Use

Abstract: Background: Asthma has been recognised as a poorly managed disease state in Australia. Rural areas have been identified as being under‐serviced by health professionals. Pharmacists in rural areas are in a prime position to be involved in the provision of multidisciplinary asthma care. Aim: This study investigated the impact of spirometry screening on asthma management by pharmacists in rural areas. Method: A two‐group (intervention: n = 141, control: n = 46) multicentre study design was utilised. The control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Our preliminary search identified a number of articles on asthma studies, but several had to be excluded as they did not screen or assess patients7,31 although some of them claimed to be assessing/screening asthma control57, or was a follow-up study 56. The review also found that although all of the included studies suggested screening for poor asthma control, critical examination of the content revealed that seven of the fifteen studies were actually assessing asthma control in every one presenting to the pharmacy with a prior diagnosis of asthma and only eight of the studies involved screening.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary search identified a number of articles on asthma studies, but several had to be excluded as they did not screen or assess patients7,31 although some of them claimed to be assessing/screening asthma control57, or was a follow-up study 56. The review also found that although all of the included studies suggested screening for poor asthma control, critical examination of the content revealed that seven of the fifteen studies were actually assessing asthma control in every one presenting to the pharmacy with a prior diagnosis of asthma and only eight of the studies involved screening.…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacy settings are effective sites for health promotion, screening and disease management services. Controlled studies have demonstrated the positive impact of pharmacist's involvement in asthma management in rural areas of Australia and New Zealand 6,7 . Globally, there is sufficient evidence to suggest that pharmacists can help improve outcomes in asthma patients 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a group of studies conducted in Australia described and assessed implementation of spirometry services for the purposes of asthma management in the community pharmacy setting (n=5). 19 , 21 , 25 , 30 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…18 , 23–25 , 29 , 30 Additionally, some studies describe other models, such as special booths, screening days or appointment-based models within the pharmacy 18 , 25 , 27 , 29 or community pharmacists participating in community health fairs or health screening events at corporate offices. 28 Several studies required that participating pharmacies have a private area where the pharmacist could meet with the patient to perform the test 20 , 24–26 , 30 (n=5) and that at least two pharmacists were on duty at all times (n=4). 19 , 20 , 25 , 29 Where it was not required, there was a trend of higher screening rates when a second pharmacist or an intern was on duty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation